Single-atom catalysts for catalytic benzene oxidation to phenol: recent progress and future perspectives. Issue 17 (4th April 2023) - Zhao, Yitao; Cao, Hongmei; Tao, Lei; Qiao, Zhiyong; Ding, Changming
Abstract : A comprehensive review with a particular focus on the significant roles of single atom sites and supports played in the substantial improvement of catalytic activity and selectivity towards the oxidation of benzene to phenol, is organized. Abstract : Single-atom catalysts (SACs), affording 100% metal dispersion and maximized metal atom utilization, have recently emerged as a new type of potential catalyst for catalytic reactions, particularly for benzene oxidation to phenol. Their great advantages have stimulated researchers' intensive endeavors toward the development of highly efficient SACs, and various metal SACs are well fabricated for facilitating the catalytic benzene oxidation reaction. Aiming to gain a better understanding of the research progress in SACs for boosting benzene oxidation into phenol in recent years, we herein present a comprehensive review with a particular focus on the roles of metal atoms and supports when used for the catalytic oxidation reactions. Additionally, the applications of many advanced SACs in benzene oxidation reactions and their structure–activity correlation are presented, which include noble-metal SACs and non-noble-metal SACs. Finally, challenges remaining in this research area are discussed and possible future research directions are proposed.